MiR-638 suppresses the progression of oral squamous cell carcinoma through wnt/β-catenin pathway by targeting phospholipase D1 - Kai-Liang Tang; Han-Ying Tang; Yi- Du; Tian Tian; Shi-Jiang Xiong (Artificial Cells, Nanomedicine, and Biotechnology)
Objective The current study aimed to explore the function of miR-638 on the progression of oral squamous cell carcinoma (OSCC) and relevant molecular mechanisms.Methods Expression profile of miR-638 in OSCC tissues and cells was detected using quantitative real-time polymerase chain reaction (qRT-PCR) method. Chi-square test was performed to estimate the relationship between miR-638 and clinical parameters of OSCC cases. Cell viability and motility abilities were estimated using MTT and transwell assays, respectively. Potential targets of miR-638 in OSCC were identified through bioinformatics analysis and luciferase reporter assay.Results MiR-638 exhibited decreased expression in OSCC tissues and cells, compared to non-cancerous controls (P < .05 for both). Moreover, its down-regulation was closely correlated with lymph node metastasis (P = .044) and TNM stages (P = .001). Enforced miR-638 expression reduced cell proliferation, migration and invasion, while its knockdown exhibited opposite effects. Phospholipase D1 (PLD1) was confirmed as a target of miR-638 in OSCC. MiR-638 could inhibit wnt/β-catenin pathway through targeting PLD1, thus realizing its anti-tumour action in OSCC.Conclusion MiR-638 may be a tumour suppressor in OSCC by targeting PLD1/Wnt/β-catenin pathway.